Molecular-genetic mechanisms of the signal cascade RAS-RAF-MEK-ERK associated with the development of the tumor process and the purpose of targeted drugs for colorectal cancer - A. N. Toropovsky; O. N. Pavlova; D. A. Viktorov; A. G. Nikitin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Colorectal cancer occupies one of the leading positions in the world in the structure of cancer incidence. The vital processes of cancer cells largely depend on the production of growth factors and their receptors. One of these is epidermal growth factor (EGFR), which is a tyrosine kinase receptor for cell membranes. Normally, binding of EGFR ligands and transforming growth factor alpha (TGFα) induces receptor activation, which triggers ERK and PI3K signaling pathways that control cell proliferation, migration, invasion, and many other processes. It was found that in 80% of cases, colorectal cancer occurs as a result of EGFR overexpression, which leads to increased growth and division of tumor cells due to hyperactivation of the RAS-RAF-MEKERK signaling cascade. The RAS-RAF-MEK-ERK cascade is a pathway that regulates cell proliferation, cell cycle, and cell migration. In the development of human cancer, mutations of the RAS/RAF family are most often the cause of dysregulation of signal transduction through this pathway. According to current data, about a third of all malignant neoplasms are associated with mutations in the genes of the RAS family, which include HRAS, KRAS, NRAS, RRAS, and other homologous proteins. Proteins of the RAS family are involved in the activation of tyrosine kinase signaling pathways, which leads to gene mutations. This process determines proliferative activity, ability to differentiate, metastasis, avoidance of apoptosis, induction of angiogenesis. Permanent RAS activation leads to malignant cell degeneration. Thus, the expression and mutation of the EGFR gene are associated with various variants of tumor progression and poor prognosis in malignant neoplasms of various localizations. Over the past decades, significant advances have been made in the treatment of metastatic colorectal cancer. However, the expansion of the spectrum of effective anticancer drugs also creates a number of difficulties in choosing the optimal drug therapy regimens in patients with metastases of colorectal cancer.